The Jews in Sicily, Volume 1 (383-1300) - Simonsohn, Shlomo, (Studia Post Biblica ;, 1997)
This volume in the series Documentary History of the Jews in Italy illustrates the history of the Jews in Sicily during the last decade of the fourteenth century and the first two of the fifteenth. It is the sequel to the first and second volumes on the history of the Jews in Sicily, and illustrates the events during the political upheavals which preceded the reunion of the island with Aragon. During that period the Jewish minority flourished, although affected by unsettled political conditions, along with the rest of the population. Over 500 documents, many of them published here for the first time, record the fortunes of the Jews and their relationships with the authorities, especially the two Martins, and their Christian neighbours. Much new information has come to light, and many facets of Jewish life in Sicily have been uncovered. The abundance of historical records in the archives of the Crown and of local authorities compares favourably with the relative scarcity of surviving documentation in earlier centuries. Therefore, again, many documents had to be reported in summary form. Much new information has come to light. The volume is again provided with additional bibliography and indexes, while the introduction has been relegated to the end of the series on the Jews of the island.